Tracking NAFTA's Shadow 10 Years On : Introduction to the Symposium - Lederman, Daniel (Published by Oxford University Press on behalf of the World Bank, 2014)
The North American Free Trade Agreement (NAFTA) is arguably the first case study of what may be expected from the increasing number of preferential trade agreements involving both developed and developing economies. Ten years after the treaty's inception, it is time to assess how its outcomes compare with initial expectations. The articles in this symposium issue provide insights into the effects of NAFTA on economic geography, trade, wages and migration, and foreign investment from Mexico's perspective. The contributions paint a complex post-NAFTA reality characterized by persistent intra-bloc trade barriers, interregional inequality within Mexico, labor market outcomes that seem closely tied to migration patterns and international trade and investment, and foreign investment flows that appear weakly related to trade agreements.